Evaluation of the Implementation of Pandeglang Regency Regional Regulation Number 4 of 2008 concerning Cleanliness, Beauty, and Environmental Order (Case Study of Menes District Square, Pandeglang Regency) - Insi Nurhayati (Epistemik Press, 2023)
The focus of this study is the Evaluation of the Implementation of Pandeglang Regency Regional Regulation Number 4 of 2008 concerning Cleanliness, Beauty, and Environmental Order (Case Study of Menes District Square, Pandeglang Regency). Identify the problem is that there are still many street vendors selling in the square, lack of supervision, lack of existing facilities, and the absence of a special budget for K3 maintenance. The theory used is the theory of policy evaluation criteria according to Leo Agustino. This research uses a qualitative approach with a descriptive method. The results of this study show that the Evaluation of the Implementation of Pandeglang Regency Regional Regulation Number 4 of 2008 concerning Cleanliness, Beauty, and Environmental Order (Case Study of Menes Subdistrict Square, Pandeglang Regency) has not run optimally because there are still many problems such as lack of involvement of the Environmental Agency, inadequate facilities, infrastructure, and technology, the absence of a special budget for K3 maintenance in Menes square, there are no sanctions against violators, and so on. Recommendations that can be given are increasing the number of personnel of the Civil Service Police Unit and Special Cleaning Officers of the Square, improving coordination between implementers, improving infrastructure and technology, collaborating with other agencies such as Department of industry and trade in structuring and empowering street vendors.